Iron age slaving and enslavement in northwest Europe - Mata, Karim (Access archaeology., 2019)
Commonly treated as a mere byproduct of incessant tribal warfare, it is generally held that slavery was not a significant phenomenon in temperate Europe before the Roman era. If slaving and enslavement can be shown to have been a significant transformative phenomena in Iron Age Europe, how would this affect the interpretation of (old and new) archaeological evidence, and how would this change ideas about broader socio-cultural developments that have long been considered known by those who have looked at these things through the lens of 'acculturation' or 'complexification'? Comparative research shows how slavery is a multifaceted phenomenon with complex interrelated material, behavioral, and ideological dimensions. This exploratory study of the dynamics of Iron Age slaving and enslaving in Northwest Europe contributes to a complex but neglected topic.